Cdc7–Drf1 kinase links chromosome cohesion to the initiation of DNA replication in Xenopus egg extracts - Takahashi, Tatsuro S. (Cold Spring Harbor Laboratory Press, 2008)
To establish functional cohesion between replicated sister chromatids, cohesin is recruited to chromatin before S phase. Cohesin is loaded onto chromosomes in the G1 phase by the Scc2–Scc4 complex, but little is known about how Scc2–Scc4 itself is recruited to chromatin. Using Xenopus egg extracts as a vertebrate model system, we showed previously that the chromatin association of Scc2 and cohesin is dependent on the prior establishment of prereplication complexes (pre-RCs) at origins of replication. Here, we report that Scc2–Scc4 exists in a stable complex with the Cdc7–Drf1 protein kinase (DDK), which is known to bind pre-RCs and activate them for DNA replication. Immunodepletion of DDK from Xenopus egg extracts impairs chromatin association of Scc2–Scc4, a defect that is reversed by wild-type, but not catalytically inactive DDK. A complex of Scc4 and the N terminus of Scc2 is sufficient for chromatin loading of Scc2–Scc4, but not for cohesin recruitment. These results show that DDK is required to tether Scc2–Scc4 to pre-RCs, and they underscore the intimate link between early steps in DNA replication and cohesion.